A calix[4]arene-based supramolecular nanoassembly targeting cancer cells and triggering the release of nitric oxide with green light - Parisi, Cristina; Ferreri, Loredana; Martins, Tassia J.; Laneri, Francesca; Sollima, Samantha; Azzolina, Antonina; Cusimano, Antonella; D’Antona, Nicola; Consoli, Grazia Maria Letizia; Sortino, Salvatore (Beilstein Journal of Nanotechnology, 2025)
We have designed and synthesized a novel calix[4]arene derivative bearing four choline appendages as recognition targeting ligands and one amino-nitrobenzofurazan as a fluorescent labelling unit at the opposite sides of the calixarene molecular scaffold. Due to its amphiphilic character, this compound is well soluble in water, forming supramolecular assemblies that are ca. 170 nm in diameter. The nanoassembly selectively targets cancer cells that overexpress the choline transporters, and it can be visualized thanks to the fluorescent tag. The fluorogenic unit also acts as a green light harvesting center, making the nanoassembly a photo-nanoreactor able to encapsulate a hydrophobic nitric oxide (NO) photodonor, otherwise activatable with blue light, and encouraging the NO release with the more biocompatible green light probably by an intra-cage photoinduced electron transfer.
Keywords: calixarenes; cell targeting; fluorescence; light; nitric oxide